A PHENOMENON WAVE OF MASS TERMINATIONS IN THE MIDDLE OF RISING ECONOMIC GROWTH IN DIGITAL BUSINESS COMPANIES (STARTUPS) AND IT’S EFFECT ON ISLAMIC EDUCATION - Effendi Sadly; Uswatun Hasanah (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The phenomenon of employee layoffs is increasingly widespread in the startup world. One by one, startups start laying off employees, from small companies to unicorns. This situation occurred when Indonesia's economic growth was rising. This study aims to discuss the causes of the emergence of waves of layoffs amid increasing economic growth and how to respond to this condition so as not to disrupt national economic stability. The method used is descriptive qualitative. The results obtained are poor management, macroeconomic pressures, and the anticipation of a global recession are the main factors for mass layoffs in the startup world. The connection with economic growth is increasing because the employment rate in other sectors has increased. The government, as the regulator, has taken swift steps to implement work-intensive programs and Vocational Skills Education to respond to the increasing number of layoffs in the startup world. Therefore, the wave of layoffs is an attempt by companies to continue to exist in the world of digital startups